2016
DOI: 10.1177/0284185115588126
|View full text |Cite
|
Sign up to set email alerts
|

Safety of gadoxetate disodium: results from six clinical phase IV studies in 8194 patients

Abstract: BackgroundSafety data on routine clinical use of gadoxetate disodium for liver magnetic resonance imaging (MRI) is not reported yet.PurposeTo assess the safety profile of gadoxetate disodium for liver MRI in the routine clinical setting.Material and MethodsSix multicenter studies were performed in Europe, USA, Australia, and Asia to evaluate the safety and efficacy of gadoxetate disodium (Primovist®/Eovist®) enhanced liver MRI. Patients received a single intravenous bolus injection of the standard approved dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The frequency of adverse events is comparable to that reported for Gd-EOB-DTPA [62]. An evaluation of six clinical phase IV studies reported that a total of 1.7% patients experienced at least one adverse event, the most frequent of which are dyspnea, nausea, and liver and renal disorders, concluding that Gd-EOB-DTPA is generally safe and well tolerated [63].…”
Section: Metal Complexes In Liver Specific Mrisupporting
confidence: 60%
“…The frequency of adverse events is comparable to that reported for Gd-EOB-DTPA [62]. An evaluation of six clinical phase IV studies reported that a total of 1.7% patients experienced at least one adverse event, the most frequent of which are dyspnea, nausea, and liver and renal disorders, concluding that Gd-EOB-DTPA is generally safe and well tolerated [63].…”
Section: Metal Complexes In Liver Specific Mrisupporting
confidence: 60%
“…However, the study of patients with moderate or severe renal insufficiency showed no systemic fibrosis progression over a retrospective 2-year period (13). Dyspnea, one of the most common side effects following administration of contrast media, is lower during the administration of gadoxetic acid (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the group of clinical studies on Gd-CM in Acta Radiologica, several phase IV, i.e. postmarketing surveillance trials, have been published on gadobutrol (Gadovist) (49), gadoterate meglumine (Dotarem) (50), and gadoxetate disodium acid (Primovist/Eovist) (51). These are all large-scale studies with >1600 patients describing the safety profile of the CM.…”
Section: Gadolinium-based Contrast Mediamentioning
confidence: 99%